2016
DOI: 10.1111/imm.12592
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR‐182 affects B‐cell extrafollicular antibody response

Abstract: SummaryMicroRNAs have been shown to play a role in B-cell differentiation and activation. Here, we found miR-182 to be highly induced in activated B cells. However, mice lacking miR-182 have normal B-cell and T-cell development. Interestingly, mutant mice exhibited a defective antibody response at early time-points in the immunization regimen when challenged with a T-cell-dependent antigen. Germinal centres were formed but the generation of extrafollicular plasma cells was defective in the spleens of immunized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 39 publications
2
30
1
Order By: Relevance
“…Overall, our results do not support the published role for miR-182 in plasmablast differentiation (28), especially the aforementioned results in Mir182 2/2 mice immunized with NP-Ficoll (Fig. 10).…”
Section: Humoral Responses To Both Ti-1 and Ti-2 Ags Do Not Depend Oncontrasting
confidence: 99%
See 2 more Smart Citations
“…Overall, our results do not support the published role for miR-182 in plasmablast differentiation (28), especially the aforementioned results in Mir182 2/2 mice immunized with NP-Ficoll (Fig. 10).…”
Section: Humoral Responses To Both Ti-1 and Ti-2 Ags Do Not Depend Oncontrasting
confidence: 99%
“…Given that miR-182 is so strongly induced upon B cell activation, yet its absence is of debatable consequence (24, 28), we sought to carefully investigate the expression of the entire 183c family. As expected (24,28), vigorous mature miR-182 induction was observed by qPCR in mature B cells stimulated ex vivo ( Fig. 1A).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Although a recent study suggested that the immune response to experimental Listeria monocytogenes infection is intact in miR-182 −/− mice 36 our results, using miR-182 −/− on the same C57BL/6 background, do suggest some alterations on the early immune response after cardiac allograft transplantation. Further, the recent studies of Li et al demonstrate that miR-182 deficiency (using knock-out mice) does impair early T cell-dependent immune responses 37 . Taken together, these studies suggest that miR-182 does have a role in T cell function, early after stimulation, but suggest after chronic stimulation/exposure the malleability of the miR networks may compensate for the loss of specific microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…does not regulate Tfh cell differentiation and function. 126 Several studies showed that miR-181a regulates the TCR signaling threshold of T-helper cells. [127][128][129][130] miR-181a is highly expressed in thymocytes, where it facilitates positive selection.…”
Section: P Otentialrole Sforother Mirna Sinthereg Ul Ati Onoftfhcelmentioning
confidence: 99%